Fostering Values-Driven Sustainability Through an Ex-Post Capacities Lens - and Cekan/ova, Jindra (Journal of MultiDisciplinary Evaluation, 2023)
Background: Ex-post evaluation of sustainability has been done for 40 years in global development. However, it has been done far less than 1% of all global development projects, for there is little proof that “sustainable” development is or is not. Similarly, foreign aid projects are implemented to foster sustainability, but without the benefit of evidence from expost evaluations of what drove it and limited research on the benefits of robust exit strategies. Purpose: Transparency in values we hold, and evaluative capacities’ best practices that we bring to our evaluations inform how they are done, with whom, and for what. Using the evidence base from ex-post evaluations and exit strategies led to these nine checklists. Professionals in monitoring and evaluation should use them to foster longterm sustainability and learning. Setting: Drawing on primary and secondary research across 91 ex-post evaluations of foreign aid sustainability plus two major studies of exit strategies globally. Research Design: The checklists were drafted based on sustainability and exit studies and then vetted with lead researchers of the two exit studies. They were revised, and additional research was done on both values-driven evaluation and evaluation competencies. Data Collection and Analysis: Some primary data was collected during ex-post evaluations by the author, complemented by secondary research. Findings: Sustained exit commitments and conditions checklists can build evaluator capacities in evaluating sustainability. Several have been used by Tufts, USAID, the GEF, and the Adaptation Fund and verified actual sustainability and its prospects.
Keywords: Ex-post evaluation; Monitoring and evaluation; Participative M&E; capacity building; capacity development; competencies; post-project; sustainability; values